Roland Barthes and communication: a necessary recovery (RuMoRes, 2012)
Interview with French professor Daniel Bougnoux, philosopher and currently emeritus professor in Communication Sciences at the University Stendhal of Grenoble (France). The interview took place after his lecture in the University of Brasília, where he spoke about the importance of classic works in the study of communication. In this sense, he traces back to the main theories of semiologist Roland Barthes in order to analyze media phenomena, in a reflexion both strict and up-to-date.